Steps toward the implementation of neurofilaments in multiple sclerosis: patient profiles to be prioritized in clinical practice - Centonze, Diego; Di Sapio, Alessia; Brescia Morra, Vincenzo; Colombo, Elena; Inglese, Matilde; Paolicelli, Damiano; Salvetti, Marco; Furlan, Roberto (Frontiers in Neurology, 2025)
Multiple sclerosis (MS) is a chronic central nervous system disease characterized by neurodegeneration and inflammation. Neurofilament light chain (NfL), a protein released during axonal injury, has gained recognition as a potential biomarker for monitoring MS progression and treatment response. Evidence indicates that blood NfL (bNfL) offers a minimally invasive, cost-effective tool for tracking neuroaxonal damage. Regular bNfL assessments can identify subclinical disease activity, guide treatment intensification, and support individualized care. However, bNfL level evaluation is currently not optimized in Italian clinical practice. This work examines the utility of bNfL monitoring in clinical practice, focusing on optimizing its use within specific patient profiles, especially in resource-limited settings. bNfL testing, particularly in targeted MS patient profiles, including stable patients exhibiting subclinical signs of disease activity, such as fatigue, and patients off-treatment, represents a promising adjunct for personalized disease management. Its integration into clinical practice, alongside MRI and clinical assessments, can enhance decision-making and improve care efficiency, especially in settings with limited MRI resources. Further research is needed to standardize testing protocols and establish disease-specific cutoffs.